Design and Synthesis of New Derivatives of (E)-3-(5-((phenylamino)methyl)-1,3,4-thiadiazol-2-yl)-2-styrylquinazolin-4(3H)-one for their Anticonvulsant Potential: Design and Synthesis of New Derivatives of (E)-3-(5-((phenylamino)methyl)-1,3,4-thiadiazol-2-yl)-2-styrylquinazolin-4(3H)-one for their Anticonvulsant Potential - Sahu, Aditya (International Journal of Pharmaceutical & Biological Archive, 2020)
Objective: The objective of the paper was to design and synthesize new derivatives of ((E)-3-(5-((substitutedphenylamino)methyl)-1,3,4-thiadiazol-2-yl)-2-styrylquinazolin-4(3H)-one and evaluated for their anticonvulsant potential. Materials and Methods: Various synthesis of (E)-3-(5-(substitutedaminomethyl)-1,3,4-thiadiazol-2-yl)-2-styrylquinazolin-4(3H)-one derivatives has been synthesized by reacting 2-substituted benzoxazin-4-one with (E)-2-(4-Substituedstyryl)-4H-benzo[d] [1,3]oxazin-4-one. All synthesized compounds have been characterized by the infrared, 1HNMR, and mass spectral analysis. Proposed compounds have been evaluated for anticonvulsant potential by subcutaneous pentylenetetrazole and maximal electroshock seizure model and compared with the reference drug phenytoin and carbamazepine. Neurotoxicity study of the synthesized compounds was also performed. Results and Discussion: The anticonvulsant evaluation of synthesized compound QNM-1, QNM-2, QNM-4, QNM-6, QNM-9, QNM-11, QNM-13, and QNM-15 has shown seizure protection at 100 mg/kg dose after 30 min and 4 h, so they have good onset of action as quickly reach brain and have prolonged action reveal that compound metabolized slowly. Whereas compound QNM-7, QNM-8, and QNM-12 were moderate active and reveal that their high concentration is required to cross blood brain barrier. Compounds QNM-3, QNM-5, QNM-10, and QNM-14 were less active. Compounds having chlorine, bromine, fluorine, and nitro in the phenyl moiety have shown good activity when attached to para group but the addition of meta and ortho group of the same may provide least active compounds and in last fluorine compounds have shown comparative less active compounds. Conclusion: The Pharmacological evaluation suggest that eight synthesized compounds have shown promising anticonvulsant potential and bulkier compounds can easily penetrate BBB to exert their effect.